Pre-service Science Teachers’ Competence and Confidence in Scientific Inquiry - R Rohandi (Universitas Sanata Dharma, 2022)
The objective of this study was to examine students’ competence and confidence in scientific inquiry. 42 pre-service science teachers were involved in completing a questionnaire. Data collected were analyzed using Rasch modeling. The results of data analysis show that mean of the Rasch score for students’ competence (1.76 Logits; SD = 1.20) is higher than the mean of the Rasch score for students’ confidence (1. 41 Logits; SD = 1.01). These results show that although students feel competent to do inquiry, they do not yet fully have the confidence to carry out inquiry learning with students in classroom activities. Implications for a science teacher and pre-service science education based on these results are discussed.